Hotel Financial Compensation System During COVID-19: A Case Study of Three-Star Hotel - Wahyu Adrian, I Gusti Agung; Tharmin, Bennet Reginald Varian; Adriansyah, Edwin (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2023)
Purpose of the study: This research aims to identify the forms and systems of financial compensation applied by hotel management during the COVID-19 pandemic. Design/methodology: This research uses a qualitative approach with a case study method. The data was obtained from observations and in-depth interviews with four key participants representing various levels of positions in the hotel. Findings: The findings showed that hotels had changed the form of financial compensation caused by the emergence of new laws and local regulations during the COVID-19 pandemic. The implementation of financial compensation by hotel management during the COVID-19 pandemic can be categorized into two forms: direct financial compensation (i.e., base pay, seniority pay, pay for performance, and person-focused pay). The second is indirect forms of financial compensation (i.e., legally required and discretionary benefits). Research limitations/Implications: The hotel should continue to pay the number of dues according to the rules that apply during the COVID-19 pandemic. By providing a direct and indirect form of compensation, the hotel is expected to increase its attractiveness in terms of employee recruitment, motivation, and retention. This research only takes a case study from one hotel categorized as a three-star hotel. Novelty/Originality of the study: This article identifies the application of the financial compensation system and how the hotel management implemented and adhered to new laws and local regulations during the COVID-19 pandemic